2006
DOI: 10.1086/509126
|View full text |Cite
|
Sign up to set email alerts
|

The Type Ia Supernova 2004S, a Clone of SN 2001el, and the Optimal Photometric Bands for Extinction Estimation

Abstract: We present optical (UBVRI ) and near-IR (YJHK ) photometry of the normal Type Ia supernova (SN ) 2004S. We also present eight optical spectra and one near-IR spectrum of SN 2004S. The light curves and spectra are nearly identical to those of SN 2001el. This is the first time we have seen optical and IR light curves of two Type Ia SNe match so closely. Within the one parameter family of light curves for normal Type Ia SNe, that two objects should have such similar light curves implies that they had identical in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 63 publications
(82 reference statements)
1
97
0
Order By: Relevance
“…The V minus NIR colours of SNe Ia are quite uniform around B maximum light. It has been demonstrated that they can be considered as a reddening estimator that is more reliable than colours obtained in the optical wavelengths (Krisciunas et al 2007). By adopting the (V − NIR) loci provided by Candia et al (2003, hereafter C03) for the slow declining SNe, we obtain E(V − J) = 0.40 ± 0.05, E(V − H) = 0.50 ± 0.07 mag.…”
Section: Direct Measurementsmentioning
confidence: 65%
“…The V minus NIR colours of SNe Ia are quite uniform around B maximum light. It has been demonstrated that they can be considered as a reddening estimator that is more reliable than colours obtained in the optical wavelengths (Krisciunas et al 2007). By adopting the (V − NIR) loci provided by Candia et al (2003, hereafter C03) for the slow declining SNe, we obtain E(V − J) = 0.40 ± 0.05, E(V − H) = 0.50 ± 0.07 mag.…”
Section: Direct Measurementsmentioning
confidence: 65%
“…Optical photometry of SN 2004S has been published by both Misra et al (2005) and Krisciunas et al (2007), with the latter authors adding a significant NIR light curve. They both found SN 2004S to be photometrically normal and we adopted a date for B-band maximum light of February 4.37 ± 0.25 (Krisciunas et al 2007). Krisciunas et al (2007) emphasize that SN 2004S andSN 2001el were found to be photometric twins.…”
Section: Observationsmentioning
confidence: 99%
“…Therefore, exactly how the group boundaries were drawn was not important. (Gerardy et al 2004), and SN 2004S (Krisciunas et al 2007); the broad-line SN 1983G (McCall et al 1984 and SN 2002er (Kotak et al 2006); and the shallow-silicon SN 1999aa , SN 1999ac (Garavini et al 2005), SN 2000E (Valentini et al 2003), SN 2005cg (Quimby et al 2006), and SN 2003fg (the proposed super-Chandrasekhar SN Ia, also known as SNLS-03D3bb; Howell et al 2006;Jeffery et al 2007a; but see also Hillebrandt et al 2007). SN 1999ac is a borderline case: in Figure 1, it falls between two core-normals, but on the basis of the shape, depth, and width of the 6100 Å absorption, we include it with the shallow-silicons.…”
Section: Introductionmentioning
confidence: 99%